2011
DOI: 10.1523/jneurosci.2840-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery after Peripheral Nerve Injury is Dependent on the Pro-Inflammatory Cytokines IL-1β and TNF: Implications for Neuropathic Pain

Abstract: IL-1␤ and TNF are potential targets in the management of neuropathic pain after injury. However, the importance of the IL-1 and TNF systems for peripheral nerve regeneration and the mechanisms by which these cytokines mediate effects are to be fully elucidated. Here, we demonstrate that mRNA and protein levels of IL-1␤ and TNF are rapidly upregulated in the injured mouse sciatic nerve. Mice lacking both IL-1␤ and TNF, or both IL-1 type 1 receptor (IL-1R1) and TNF type 1 receptor (TNFR1), showed reduced nocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
233
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(255 citation statements)
references
References 36 publications
18
233
3
1
Order By: Relevance
“…This indicated that the algogenic effect of microgliaderived MVs was mediated, at least partly, by IL-1β. This is in agreement with previous reports that IL-1β acts as a mediator of supraspinal circuits of pain in neuropathic conditions [46][47][48].…”
Section: Discussionsupporting
confidence: 94%
“…This indicated that the algogenic effect of microgliaderived MVs was mediated, at least partly, by IL-1β. This is in agreement with previous reports that IL-1β acts as a mediator of supraspinal circuits of pain in neuropathic conditions [46][47][48].…”
Section: Discussionsupporting
confidence: 94%
“…Quantification of the Ly6C hi and Ly6C lo monocyte subsets supported the premise that the anti-Ly6G treatment did not affect any of them, indicating that 1A8 specifically depletes circulating neutrophils and spares the monocyte populations (Fig. 3E, 3F), in agreement with previous reports (43,48). As a point of interest, the administration route was a critical factor for keeping mice healthy in depletion experiments.…”
Section: Neutrophils Are Eliminated From the Circulation Of Eae Mice supporting
confidence: 90%
“…For multicolor immunofluorescent labeling, cells were incubated on ice with mouse Fc block (i.e., purified anti-mouse CD16/CD32; BD Biosciences) for 15 min to prevent nonspecific binding, followed by labeling for 30 min on ice with the following fluorescently conjugated primary Abs (all from BD Biosciences except where noted): anti-CD45 PerCP (dilution, 1:100), anti-CD11b Alexa Fluor 700 (1:100), anti-Ly6C BD Horizon v450 (1:167), anti-Ly6G PE-Cy7 (1:100), anti-F4/80 allophycocyanin (1:25), anti-CD3e PE-CF594 (1:100), and anti-7/4 PE (1:40, AbD Serotec) (for a full description of some of these primary Abs, please refer to our published work; see Ref. 43). As for the blood samples, the Live/Dead fixable yellow dead cell stain kit (Life Technologies) was used to distinguish live from dead cells.…”
Section: Spinal Cords Preparationmentioning
confidence: 99%
“…Neutrophils are the first immune cells migrating towards the injury site. Their numbers peak at 24 hours following peripheral nerve injury and decrease progressively after three days post-injury, but still remain significant for at least one week (Nadeau et al, 2011). Infiltrated neutrophils in injured nerves play an important role at the very early stages of neuropathic pain through the release of pro-inflammatory mediators, such as cytokines TNF-, IL-1 and IL-6 and reactive oxygen species, which are involved in regulating neuronal excitability (Schafers et al, 2003).…”
Section: Infiltration Of Immune Cells Into Injured Peripheral Nervesmentioning
confidence: 99%
“…Systemic treatment of sciatic nerve injured mice with a monoclonal antibody against the Ly6G antigen specifically expressed by neutrophils demonstrated that depletion of neutrophils attenuates the development of neuropathic pain behaviour (Nadeau et al, 2011). Furthermore, using molecular and pharmacological approaches, partial or complete depletion of macrophages yield beneficial effects in alleviating nerve injury associated chronic pain.…”
Section: Depletion Of Neutrophils or Monocytes/macrophages Impairs Nementioning
confidence: 99%